Duration of immunity against infectious rhinotracheitis and bovine viral diarrhea after vaccination in calves in southern region of Kazakhstan - Bulatov, Yerbol; Sametova, Zhanna; Abitayev, Ruslan; Kyrgyzbayeva, Asselya; Ussembay, Abdurakhman; Kondibaeva, Zhanat; Amanova, Zhanat; Turyskeldy, Sholpan; Toktyrova, Dariya; Mazbayeva, Dana; Shorayeva, Kamshat; Jekebekov, Kuanysh; et al. (Frontiers in Veterinary Science, 2025)
Some of the most economically significant viral infections affecting cattle globally include infectious bovine rhinotracheitis (IBR) and bovine viral diarrhea (BVD). Both viruses cause a wide range of clinical consequences and significant economic losses. Recent serological surveillance in Kazakhstan showed that these infections persist despite commercial vaccines, underscoring the need for more effective, locally appropriate immunization protocols. This study aimed to evaluate the duration of immunity conferred by a developed associated inactivated emulsion vaccine against IBR (strain “R-93”) and BVD (strain “Oregon C24V”), produced by the Research Institute for Biological Safety Problems. In the southern region of Kazakhstan. Of the 12 seronegative for BoHV-1 and BVDV clinically healthy crossbred calves (Friesian-Holstein and Kazakh Whiteheaded) eight were vaccinated, revaccinated, and monitored over a 9-month period for evaluation of the vaccine. Humoral immune responses were assessed using enzyme-linked immunosorbent assay and virus neutralization assays. Specific antibodies to BoHV-1 and BVDV were detected as early as day 7 post-vaccination, with titers peaking at 6.16 log2 and 6.24 log2, respectively, by day 28, and remaining above protective levels for at least 6 months. At 9 months, a challenge was conducted using virulent strains: no clinical signs or lesions in vaccinated animals, fever and respiratory systems in unvaccinated animals. These findings suggest that the tested inactivated vaccine is safe, immunogenic, and capable of providing sustained protection in crossbred cattle under local climatic conditions. Although the sample size was limited, the results allow us to make preliminary conclusions about the vaccine’s efficacy; however, further large-scale studies are needed.